Morphological and Molecular Analysis Describing Two New Species of Myxobolus (Cnidaria, Myxosporea) in Mugil curema (Mugilidae) from Brazil † - Vieira, Diego Henrique Mirandola Dias [UNESP]; Osaki-Pereira, Melissa Miyuki [UNESP]; Abdallah, Vanessa Doro; Oliveira, Sarah Letícia Paiva; Duarte, Aline Gabriely Torres; da Silva, Reinaldo José [UNESP]; de Azevedo, Rodney Kozlowiski (MDPI, 2024)
We present descriptions of two newly discovered species of Myxobolus (Myxobolidae) that infect Mugil curema: Myxobolus mundauensis n. sp. found in gills and Myxobolus patriciae n. sp. found in intestines. These descriptions are based on the morphology of myxospores, histological analysis, and sequencing of the small subunit ribosomal DNA (ssrDNA). The myxospores of both species differ in the width and length of their spore bodies, and their ssrDNA sequences showed a 10.6% difference. These findings support the identification of these parasites as distinct and previously unknown species. Phylogenetic analysis revealed a subclade consisting of species that parasitize Mugiliformes, with Myxobolus mundauensis n. sp. being closely related to Myxobolus maceioensis, and Myxobolus patriciae n. sp. being closely related to Myxobolus curemae. Our analysis aligns with previous research suggesting a strong correlation between host orders and phylogenetic patterns within the Myxobolidae family.
Keywords: molecular analysis; Mundaú Lagoon; Myxobolus mundauensisn. sp; Myxobolus patriciaen. sp; phylogeny; taxonomy